Studying self-fertility in new black currant cultivars from the VIR collection in Northwestern Russia - O. A. Tikhonova (Труды по прикладной ботанике, генетике и селекции)
Background. An important task is to search for and select highly self-fertile cultivars for plant breeding programs and for setting single-cultivar plantings in commercial horticulture.Materials and methods. Cultivars were assessed for their self-fertility levels at Pushkin and Pavlovsk Laboratories of VIR in 2019–2022. Thirty black currant cultivars of eight genetic groups served as the research material. Their levels of self-fertility were tested using conventional techniques. Free pollination served as the control. The resulting data were analyzed according to the main indicators crucial for precise characterization of a cultivar’s self-fertility level: fruit setting rate, berry weight, seed yield, and fertilization effectiveness. The data were statistically processed using Microsoft Excel and the guidelines by B. A. Dospekhov. Fruit setting rate, berry weight, seed yield and fertilization effectiveness were considered for each pollination variant.Results and conclusion. Cultivars with high and stable self-fertility levels were identified as potential valuable sources for breeding programs: ‘Partizanka Bryanskaya’ (k-45548), ‘Ben Gairn’(k-45524), ‘Litvinovskaya’ (k-45542), ‘Mushketer’ (k-45544), ‘Raduzhnaya’ (k-45549), ‘Ben Lomond’ (k-32611), and ‘Vertikal’ (k-45528). Cvs. ‘Partizanka Bryanskaya’ (k-45548), ‘Ben Gairn’ (k-45524), ‘Mushketer’ (k-45544), and ‘Vertikal’ (k-45528) may be used in single-cultivar plantings because they are able to set the same number of berries under natural self-pollination and free pollination. Natural self-pollination (autogamy) led to a decrease in the size of berries and the number of seeds in them. An increase in the main self-fertility indicators was observed under artificial self-pollination and free pollination.